The molecular mechanism of insulin action in human theca and adipocyte cells in polycycstic ovarian syndrome - Cadagan, David (2013)
PCOS is one of the leading causes of infertility worldwide affecting 1 in 10 women of a reproductive age. One of the fundamental abnormalities in women with PCOS can be seen within hormonal irregularities, which may include hyperandrogenemia hyperinsulinemia and hyper secretion of luteinising hormone (LH); and it is hypothesised that a defect in steroid secreting ovarian theca cells is involved due to their contribution in non-PCOS hormonal synthesis. Hyperinsulinemia has been associated with hyper-androgenemia through in vitro studies of cultured PCOS theca, where it has been suggested that insulin increases progesterone and androstenedione secretion when compared to normal theca cells. Furthermore the augmented effects of LH and insulin have been seen to increase ovarian androgen synthesis in non-PCOS theca cultures whilst also increasing the expression of steroidogenic enzymes specific to the PI3-K pathway. Many theories exist toward the etiology of hyper androgenemia within PCOS. Very few approaches however, consider dysfunction in multiple tissue types that may contribute to hormonal imbalances. It is well established that an association between obesity and PCOS exists and it is often the first therapeutic target for re-establishing reproductive function in obese PCOS patients. Furthermore PCOS patients tend to show distinct gynoid body fat distribution, which is reported to aggravate PCOS symptoms. It was therefore valid to examine the involvement in adipocyte function and its contribution to androgen levels within peos. This is further supported through the link between metabolic disorders such as insulin resistance and hyperinsulinemia, and their associations to obesity. Our study employed isolated preadipocyte and thecal cultures with close regulation of the influential factors LH and insulin. In doing so, we analysed androgen synthesis through activation and expression of steroidogenic enzymes CYP17 within both normal and polycystic ovaries. This allowed us to examine whether protein/hormonal concentrations vary across non-PCOS and peos cultures. This also allowed us to examine the possibility of a novel pathway leading to localised adipocyte synthesis as well as pinpointing whether dysfunction existed within the insulin-signalling pathway of thecal androgen steroidogenesis. The work in this thesis shows that adipocytes derived from non-PCOS and PCOS women, maintained in vitro differ on the basis of their morphology, rates of differentiation and proliferation. Furthermore, they reacted differently under conditions designed to mimic PCOS in vitro (increased insulin and LH), with reduced non-PCOS proliferation, and increased non-PCOS androgen secretion on insulin treatment. We also found increased steroidogenic CYP 17 expression in PCOS cultures under insulin stimulation. However PCOS adipocytes androstenedione secretion remained unaffected by insulin stimulation and secreted constant levels of androstenedione similar to that seen by insulin stimulated non-PCOS adipocytes. Our examination of non-PCOS and PCOS primary thecal cultures showed CYP17 expression is increased in pcas theca under basal conditions and that increases in insulin and LH leads to increases in in vitro theca proliferation. These conditions were also seen to lead to significant increases in androstenedione secretion over non-PCOS thecal cultures, and the results suggest it to be acting through the PI3-K pathway. These results therefore point to a specific area of dysfunction that should be further targeted for examination. Furthermore, they suggest that an adipocyte dysfunction exists within PCOS patients that may significantly contribute to hyperandrogenemia through localized synthesis of androgens.